Free daycare and its effects on children and their families - Busse, Anna; Gathmann, Christina (SOEP papers on multidisciplinary panel data research, 2017)
Many governments invest substantial public funds to foster early childhood education. And yet, there are still many open questions who responds to and who benefits from public investments into early childcare. We use the introduction of free public daycare in German states to analyze its effects on children and their families. Our results suggest that effects of the policy differ by child age, gender and socio-economic status. Free daycare increases attendance among 2-3 year olds with little response among older children. Yet, even with access to free daycare, we find few effects on maternal labor supply. Responses are generally stronger for poorer households and other vulnerable families. Child development, in turn, shows gender-specific effects that are in part explained by the differential choices parents of boys make compared to parents of girls.